Growth and Yield of Okra (Abelmoschus esculentus (L.) Moench.) as Affected by Okra Population and Weeding Regime in Abeokuta, Ogun State, Nigeria - Osunleti (2025)
Initial slow growth of okra makes them highly susceptible to weed interference with high yield losses. Therefore, adequate plant population and timely weeding become necessary for enhanced productivity. Hence, growth and yield of okra as affected by okra population and weeding regime was evaluated. The study was conducted using a split–plot arrangement, fitted into a Randomised Complete Block Design (RCBD) and replicated three times. The main plot consisted of three plant population: 33 333 plants.ha-1, 44,444 plants.ha-1 and 66 667 plants.ha-1. The subplot was four levels of weeding regimes: no weeding; weeding at 3 weeks after planting (WAP); weeding at 3 and 6 WAP; weeding at 3, 6 and 9 WAP. Data collected were subjected to Analysis of Variance, and significant means were separated using least significant difference (LSD at p ≤ 0.05). The results showed that planting okra at 66 667 plants.ha-1 resulted in significantly lower weed infestation. Similarly, weeding okra thrice at 3, 6 and 9 WAP resulted in the lowest values of weed parameters. While planting okra at 66 666 plants.ha-1 gave the highest okra stands and vigour, okra planted at 33 333 plants.ha-1 and 44 444 plants.ha-1 produced bigger and longer okra pods than planting at 66 667 plants.ha-1. Highest okra yield was recorded with weeding at 3, 6 and 9 WAP. In this study, uncontrolled weed infestation caused 99 % yield reduction. Hence, for minimum weed infestation and optimum okra yield, okra should be planted at 44 444 plants.ha⁻¹ and weeded three times at 3, 6 and 9 WAP.